Klasztor w Ołoboku w badaniach archeologicznych roku 1997 - Andrzejewski, Aleksander; Kajzer, Leszek; Lewandowski, Marcin (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The objective of preliminary field works conducted in 1997 on the ground of former female Cistercian cloister in Ołobok was to define the size of its original, not preserved foundations and to make plans for future studies as far as architectural history of the object is concerned. The project included studies on the cloister hill stratigraphy and defining the width and range of eastern and northern wing of the claustrum. On the total area of 120 m2 (the cubature exceeded 300 m3) along Tour rows six examination ditches were dug and 108 drills made, with the use of geological drill. Excavations brought 8886 specimens of portable relic material, irregularly distributed in individual examination units. Relics occurred mainly in deposits beyond the confines of the cloister buildings. Finds from Ołobok collected during examinations demand further comparative analyses. Although the observations may undergo slight changes during further studies, preliminary characteristics of the relics can be presented now. The largest group of the total number of 4818 relics is constituted of fragments of clay vessels. Among the finds there were: 1394 fragments of window and vessel glass, 1211 fragments of stove tiles (among them 1102 fragments of plate tiles), 18 fragments of building ceramics, 305 metal articles (mainly nails, hooks, etc.) and 1123 animal bones. According to preliminary analyses the collection of portable finds illustrates mainly the process of functioning of the cloister unit in its baroque phase. Excavations did not bring relics which would enable to illustrate the issue of the material culture of the Ołobok female Cistercians in the Middle Ages. Although the present works have not provided us with new knowledge about architectural transformations of the cloister in Ołobok , and although it has become obvious that because of a complete destruction of the foundation parts of the monastery it would never be possible, the collected data have allowed to acknowledge that in late Middle Ages the Ołobok unit was entirely made of wood. Traces of the late Mediaeval phase were observed only marginally. It should be assumed that the remains of constructions and the ground layers were totally damaged during subsequent building works. Masonry church and a claustrum of undefined spatial form were raised at the end of the 15th or at the beginning of the 16th century. Late gothic cloister was probably totally pulled down in the 17th century and on its place the first baroque foundation was raised. Probably at that time was built a quadrilateral unit of buildings concentrated around elongated viridarium, although that spatial form might have equally well been connected with the second baroque reconstruction, which took place since the 2nd half of the 18th century. Also at that time the Ołobok ’’palace" of female abbots was founded. A total demolition of cloister buildings took place in 1882 and led to a complete disappearance of relic masonry structures. Therefore, the cognitive value of the object is very much limited and regarding its stratigraphy a full reconstruction of the cloister foundations in the respecting stages of its functioning will not be possible.